Impact of Non-Cash Payments on the Economic Growth of Sri Lanka - Mithila, G.; Lingesiya, K. (Faculty of Business, NSBM Green University, 2024)
There has been extensive discourse on the topic of cashless payments, and their global adoption has witnessed exponential growth in recent years. Cash transactions pose certain challenges, notably the impracticality of managing physical currency and the restricted accessibility of financial institutions to withdraw cash. Multiple research studies have affirmed the positive influence of cashless payments on economic growth, thus highlighting their crucial significance. The present study aims to examine the effects of cashless payments on the economy of Sri Lanka. In particular, the investigation focuses on the measurement of economic growth using the real Gross Domestic Product (GDP), and the analysis of cashless payment systems through the employment of Real-time Gross Settlement System (RTGS), Cheque (CHE), Sri Lanka Interbank Payment System (SLIPS), and Internet Banking (IB), Mobile Banking (MB), Credit Card (CC), Debit Card (DC) transactions as representative indicators. The data utilized in this study is based on secondary sources in the form of time series data, spanning from quarter 01 of 2015 to quarter 3 of 2022. The AutoRegressive Distributed Lag (ARDL) model is then employed for the purpose of data analysis. Upon conducting an analysis of the long-term impact of various payment methods on economic growth, it is determined that RTGS (94% of total digital transaction) and SLIPS have a statistically significant positive relationship with economic growth. Conversely, IB exhibits a significant negative relationship which requires targeted improvements. Notably, there is no significant impact on economic growth observed with respect to the CHE, CC, DC, and MB indicating the need for technological advancements and integration. In the short run, it can be inferred that there is a significant positive correlation between RTGS, CHE, IB, and MB. Conversely, the analysis indicates a significant negative relationship between the SLIPS and DC payment methods. It is worth noting that the analysis does not reveal any significant association between the CC payment method and economic growth. Hence, this study conclude that digital currencies have on overall positive impact on short and long run in Sri Lankan economic growth and highlights the importance of prioritizing efficient payment systems that foster the economic growth while addressing the challenges with less effective methods. Policy makers and financial institutions can enhance the efficiency of payment ecosystems, ultimately driving sustainable economic growth.
Keywords: Auto Regressive Distributed Lag (ARDL); Cointegration; Error Correction Models; Cashless Payments; Economic Growth; Unit root Test